"Bevrydende waarheid?" Nagedink oor die aard van gereformeerde belydenis - D. J. Smit (Acta Theologica)
This article pays tribute to the honouree by reflecting on the nature of Reformed confession, including confessional documents as well as rich and complex ways of confessing. A first section argues that the Reformed tradition is by its very nature a confessional tradition, although confession is to be taken in a broad sense, and confessional documents can serve many and diverse purposes and needs. A second section discusses some aspects of the nature of Reformed confession by focusing on issues related to the authority of confessional documents — their relation to Scripture, their historical, contextual and linguistic nature, the fact that they are human products and therefore fallible, as well as the need for ongoing confession and the possibility of new situations calling for new forms of confession. A final section underlines the intimate relationship between confession and embodiment — both ecclesiologically and ethically— according to the Reformed understanding of the nature of confession.